Herbs and spices in aging - Mohamed, Suhaila (Elsevier, 2014)
Herbs and spices are rich in bioactive antioxidants, dietary fibers, proteins, minerals, vitamins, phytochemicals and sometimes unsaturated fatty acids. Traditionally, herbs and spices are used as flavoring and culinary agents in food, and as medicine. Recent research has confirmed and revealed their therapeutic and protective effects for health and disease management in various animal models and clinical studies. The diseases include cardiovascular ailments, cancer, cataracts, macular degeneration, diabetes, hypertension, dyslipidemia, stroke, inflammation, and cognition impairment. Many of these diseases can be considered as diseases of aging as their incidence increases, markedly as people age, and such diseases contribute to high rates of morbidity and mortality in the elderly. Some active compounds and modes of action have been identified and compiled. The herbs and spices covered in this chapter include cloves, saffron, turmeric, ginger, oregano, cinnamon, cumin, black pepper, Vitex negundo, Moringa olefera leaves, fenugreek, chili, pennywort, Ginkgo and seaweeds